ISLAM OF THE ARCHIPELAGO: COSMOPOLITANISM OF ISLAMIC CIVILIZATION IN INDONESIA - Lukman S. Thahir (Islam Futura, 2021)
This paper elucidates and analyses one of the Muslim intellectual heritage in Indonesia which is phenomenal and cosmopolitan, what is called Islam Nusantara (Islam of the Archipelago). When reading the history of the arrival of Islam in Archipelago, most of the scholars studying Archipelago Islam agreed that Islamization of this area was conducted in a peaceful way. They assimilated and complemented each other to become what is called “citizen of the world”. Derridas called this as a model of universal hospitality or guiding principle to protect people from wars. As a religion of peace, Islam is cosmopolitan. This is proved by the fact that Islam is a religion which includes races and nations. This feature is marked by Nine saints (Walisanga) as Javanese unique agents in the fifteenth and sixteenth centuries, taking interactionist approach between Islam and local culture. This in turn creates Indonesian Islamic civilization which is called today “Islam Nusantara”, Islam without such obstacles as culture, religion, and nation, Islam with a peaceful face that respects humanity and emphasizes tolerance and empathy to human beings.